Nowcasting Pergerakan Indeks Saham Lingkungan Berdasarkan Minat Publik terhadap Isu Lingkungan - Zareka, Andi Muh. Zulfadhil; Ayuningrum, Adinda Safira Santoso; Adnyana, I Kadek Surya Wisesa; Kurniawan, Robert (Politeknik Statistika STIS, 2025)
The growing awareness among investors regarding environmental, social, and governance (ESG) aspects has increased attention toward the performance of environmentally-based stock indices. This condition has created a need for a nowcasting approach that is responsive to real-time public interest dynamics and market sentiment. This study aims to analyze public interest in environmental issues measured using Google Trends web search volume as a proxy for collective sentiment in predicting the movement of environmental stock indices. ARIMAX, SARIMAX, Random Forest, SVR, and XGBoost models are implemented and evaluated for their performance in predicting index movements. The results show that SVR, with an RMSE of 20.3646, is the best-performing model. These findings indicate that public interest in environmental issues has significant potential as an effective indicator for real-time prediction of environmental stock index movements, offering valuable insights for investors and market analysts in developing investment strategies that are more responsive to market dynamics influenced by sustainability factors.